Over the counter (OTC) sell of sex enhancer drugs: an emerging public health issue in India - Debaje, Samadhan Prakashrao; Hiremath, Renuka C. (International Journal of Research in Medical Sciences, 2017)
Background: As a result of lack of skilled service providers/doctors, there is increasing trend of over the counter (OTC) sell of medicine in India. Among these OTC drugs, sell of sex enhancer medicine is an emerging problem as these medicines are being advertised on large scale using mass media like Television, newspapers and Radio without any approval from drug controlling authority ‘Central Drugs and Standards Control Organization’. Purpose of current study was to study the trend of over the counter sell of sex enhancer drugs in India & to study health seeking behavior of patients with self-diagnosed ED in terms of self-medication. Methods: This cross-sectional study include interview schedule of 74 patients coming on 10 medical stores selected randomly in Jodhpur city in September 2013. Results: So 10% were found to buying sex enhancer drugs. Thirty eight percent among those buying sex enhancer medicines were Unmarried and 62% were married.92% buying sex enhancer medicine were Hindu and 8% were Muslim patients. Only 9.46% patients had consulted allopathic doctors and 12.16% consulted to Ayurveda Vaidya, 4.05% consulted local Quack and 8.11% consulted to friends but 66.22 % patients had not consulted anybody for Medication; but they are buying by self for self-diagnosed ED Conclusions: This study therefor confirms that there is significant association between self-diagnosed ED and OTC sell of sex enhancer medicine in India. TV & newspapers, poster/banners are significantly important in providing information of sex enhancer medicines to self-diagnosed patients of ED.